(untitled) (Journal of Engineering, 2006)
The low order panel method with Neumann boundary condition have been used to predict the normal force curve slope, the pitching moment curve slope, the center of pressure location and the aerodynamic load distribution for missile in compressible, steady flow. The wing-body-canard interference problem have been solved using two schemes (iterative method and internal singularity method) both are based on the panel method. The normal force curve slope, the pitching moment curve slope and the center of pressure location for a given missile has been predicted using the present numerical method and the DATCOM technique.